Influence of the overseas on-the-job training program in the student’s employability - Evelyn Q. Alera; Honeylet J. Nicolas; Ryan P. Ceniza; Maria Adela B. Chaves; Cindy S. Cruz; Aisanne Marie S. McNatt (International Journal of Evaluation and Research in Education (IJERE), 2026)
The study investigated the influence of the overseas on-the-job training (OJT) program in the employability of the students of three undergraduate degrees, namely Bachelor of Science in Agriculture (BSA), Bachelor of Animal Science (BAS) and Bachelor of Science in Agribusiness Management (BSAM) in an agricultural state college. A validated instrument was used to survey a sample of 47 trainees. Findings of the study demonstrated a significant positive correlation between the impacts of the overseas OJT and the measured employability skill set. Personal qualities, work attitude and habits, work performance, and professional skills are all construed to be effectively improved by the trainees’ involvement and admission to the overseas OJT program. The perceived effectiveness in the employability skill is also evidenced in the high employment rate of the graduates and the high percentage of them being employed in the field connected to their degrees. The study also strengthened the findings from other internship reports that both soft skills and hard/technical skills are valued greatly when it comes to securing employment. The present study is the first local documentation of the insights of the trainees who participated in the Agrostudies which consolidated their learned skills and raised their concerns on the implementation of the said training program. From here, it is recommended that further studies are to be conducted to validate the present findings and an in-depth review of the underlying issues of the trainees should be addressed to ensure the success and continuity of the program.